MENGUNGKAP NILAI PENENTUAN HARGA JUAL VIRTUAL ITEM GAME AVABEL ONLINE: STUDI FENOMENOLOGI - Haryadi, Bambang; Hery, Andi (LP2M Institut Teknologi dan Bisnis Asia Malang, 2023)
This research aims to find out the values behind determining the selling price of virtual items, using a qualitative method in the form of a phenomenological approach. The approach was chosen because researchers need depth to reveal the reality behind the phenomenon. Informants in the study were business people and virtual item customers. The research plunges directly into the game as a player and finds out information directly. The results showed that the practice of determining the selling price of virtual items that occurred had several concepts in common with the theory, namely in the calculation of the cost of production. But coupled with the treatment of a sense of friendship in determining prices. This sense of friendship is manifested in the form of selling price